Lukman Batik: Experiencing Batik Making in Cultural Heritage Site - Rianandita Sari, Nanik; Ariebowo, Teguh; Kusuma, NurMakkie Perdana (Bina Nusantara University, 2024)
The research discussed Lukman Batikâ€™s artwork, which served as a poignant reminder of the value of maintaining these traditions and ensuring that traditional techniques and patterns used in batik art were practical and could be carried on by future generations. The research aimed to conduct thorough research on Lukman Batik Yogyakarta and its significance as a cultural heritage site, to investigate the correlation between prior knowledge and cultural tendency in relation to the tourist experience of making batik at Lukman Batik Yogyakarta, to analyze the data collected and interpret the nature of the correlation between prior knowledge, cultural tendency, and tourist involvement in experiencing batik making at Lukman Batik Yogyakarta. The research was analyzed using Pearson correlation. The target audience of the survey was tourists who came to Lukman Batik, and the sample was 732 tourists aged 17-50 years old. The sampleâ€™s statistical analysis showed that the respondentsâ€™ sex ratio was generally balanced, with a majority of young and middle-aged (age 17-45 years old) tourists. The majority of participants had bachelorâ€™s degrees or above, and the majority of respondents were professionals or employees. The research reveals that 0.949, which means that prior knowledge has a â€œvery strongâ€ relationship with cultural tendency and involvement. The result shows a significant positive relationship between prior knowledge and the cultural tendency of tourist involvement. Interaction with cultural attractions, such as batik making and tourist participation throughout the visit, play a major role in forming enduring memories.